Methamphetamine-Induced Bowel Ischemia in a 50-Year-Old Male - Brian Kurtz; Abdalhai Alshoubi; Katrina Nguyen; Eric Gehres (Case Reports in Critical Care)
Methamphetamine intoxication is a known risk factor for nonocclusive mesenteric ischemia (NOMI). We describe a case of a 50-year-old male with a history of polysubstance abuse who presented to the Emergency Department with severe abdominal pain and coffee-ground emesis. Computed tomographic (CT) imaging demonstrated portal venous gas and diffuse colonic wall thickening concerning for ischemic colitis. The patient underwent exploratory laparotomy with resection of the ascending colon as well as a necrotic section of the jejunum. Further embolic workup was negative with a subjective history of amphetamine use prior to presentation. NOMI has a high fatality rate, and we recommend providers include drug-induced bowel infarction on their differential when presented with findings of ischemic bowel of unclear etiology.